UU RI No.11 Th.1998 tentang perubahan berlakunya UU No.25 Th.1997 tentang ketenaga kerjaan - [Tidak Terdaftar] (Cipta Jaya, 1998)
UU RI No.11 Th.1998 Tentang perubahan berlakunya UU No.25 Th.1997 Ketenagakerja